2009
DOI: 10.1108/10610420910957799
|View full text |Cite
|
Sign up to set email alerts
|

Searching for competitive advantage with the aid of the brand potential index

Abstract: Purpose -In recent years, the world food market has undergone an accelerated process of concentration and consolidation. These intensive processes increase the competitive advantage of operating activities on the global market and are the result of numerous changes in the period of new economy. What is the meaning of brand management and how is it dealt with in practice? What is the importance of positioning in the light of brand image and identity? Which are the ways to measure the brand strength with the aid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 2 publications
0
14
0
6
Order By: Relevance
“…Details of these research methods can be found in Gacula and Singh (1984), Malhotra et al (1999), Žižmond and Novak (2006) and Vukasovič (2009b;. Details of these research methods can be found in Gacula and Singh (1984), Malhotra et al (1999), Žižmond and Novak (2006) and Vukasovič (2009b;.…”
Section: Research Design and Data Collectionmentioning
confidence: 99%
“…Details of these research methods can be found in Gacula and Singh (1984), Malhotra et al (1999), Žižmond and Novak (2006) and Vukasovič (2009b;. Details of these research methods can be found in Gacula and Singh (1984), Malhotra et al (1999), Žižmond and Novak (2006) and Vukasovič (2009b;.…”
Section: Research Design and Data Collectionmentioning
confidence: 99%
“…The consumer goods market has undergone an accelerated process of concentration and expansion. These intensive and extensive processes of managing existing and new markets have activated competitive brands in urban areas, resulting in shifts in the behavior of consumers in urban habitats (Vukasovic, 2009). The conventional branding strategies of multinational firms have experienced continuous refinement in reference to changing business dimensions to gain competitive advantage.…”
Section: Managing Brand Thrustmentioning
confidence: 99%
“…These intensive and extensive processes of managing existing and new market have activated competitive brands in urban resulting into market and are resulting into shifts in the behaviour of consumers in urban habitat (Vukasovic, 2009). Consumer goods market has undergone an accelerated process of concentration and expansion.…”
Section: Managing Brand Thrustmentioning
confidence: 99%